2018
DOI: 10.1097/ccm.0000000000003272
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Seizure Medication and Health-Related Quality of Life After Intracerebral Hemorrhage

Abstract: Prophylactic levetiracetam was independently associated with lower cognitive function health-related quality of life at follow-up after intracerebral hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…Recent studies have suggested that prophylactic Levetiracetam for patients with intracerebral haemorrhage was independently associated with lower cognitive function on follow-up [22]. We hope to assess the extent that prophylactic AEDs in TBI impacts long-term cognitive function in future work.…”
Section: Percetage Of Patientsmentioning
confidence: 99%
“…Recent studies have suggested that prophylactic Levetiracetam for patients with intracerebral haemorrhage was independently associated with lower cognitive function on follow-up [22]. We hope to assess the extent that prophylactic AEDs in TBI impacts long-term cognitive function in future work.…”
Section: Percetage Of Patientsmentioning
confidence: 99%
“…One of the largest prospective multicenter studies showed the overall incidence of seizures to be about 10.6% following ICH and about 8.6% following ischemic strokes [16]. Additional studies showed seizure activity to be present in up to 10–25% of patients following ICH [32,33], and about 15.2% after SAH [30]. A large recent meta-analysis that did not differentiate from ischemic versus hemorrhage reported an overall 7% risk of stroke-related seizures [7].…”
Section: Incidence Of Post-stroke Seizuresmentioning
confidence: 99%
“…A vast majority of patients experience adverse effects on ASMs, including cognitive slowing, mood problems, and gait instability 18–21 . ASMs interact with other medications, 22 and negatively affect the quality of life after stroke 23 . Therefore, there is a need to better understand the long‐term use of ASMs in stroke patients.…”
Section: Introductionmentioning
confidence: 99%